Low-platinum-loaded Pt / NiFe (CN) 5NO self-supporting electrode as well as preparation method and application of low-platinum-loaded Pt / NiFe (CN) 5NO self-supporting electrode

Pt/NiFe(CN)5NO self-supporting electrode was prepared on the platinum sheet substrate by anodized coupling electrodeposition method, which solved the problem of low oxygen evolution reaction rate and easy catalyst fall off, and achieved efficient and low-cost electrolytic catalytic effect.

CN120575253APending Publication Date: 2025-09-02ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510768852.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The kinetic rate of the oxygen evolution reaction during the existing water decomposition process is low, resulting in high overpotential, increasing the energy consumption and cost of hydrogen production by electrolyzing water. In addition, traditional powdered catalysts are prone to fall off, affecting the electrocatalytic performance.

Method used

Using anodized coupled electrodeposition method, Pt/NiFe(CN)5NO self-supporting electrode is prepared on a platinum sheet substrate. By controlling the electrochemical reaction conditions, co-deposition of nickel, iron and platinum is achieved to form a nanosheet structure.

Benefits of technology

The overpotential of the oxygen evolution reaction is reduced, catalytic activity and stability is improved, the use of binders is avoided, the electrode processing is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120575253A_ABST
    Figure CN120575253A_ABST
Patent Text Reader

Abstract

The invention discloses a low-platinum-loaded Pt / NiFe (CN) 5NO self-supporting electrode as well as a preparation method and application of the low-platinum-loaded Pt / NiFe (CN) 5NO self-supporting electrode. A platinum sheet is used as an anode, a hydrochloric acid aqueous solution of nickel chloride and potassium ferricyanide is used as an electrolyte, and a Pt / NiFe (CN) 5NO self-supporting electrode is obtained by deposition at a cathode through an electrochemical anodic oxidation coupling electrodeposition reaction; the electrode has excellent oxygen evolution performance, self-supporting electrodes with different structures and compositions are obtained on the metal surface by controlling electrolyte components, reaction temperature, reaction voltage and reaction time, and the electrocatalytic activity and stability of the composite self-supporting electrode are improved; while the deposition amount of platinum is controlled, nickel and iron elements are compounded, the oxygen evolution performance of the self-supporting catalyst is improved by utilizing a synergistic effect, the problem of agglomeration or falling of the catalyst is avoided, the catalytic activity is enhanced, and the self-supporting catalyst has a wide application prospect in the aspect of industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical materials, and in particular to a low-platinum-loaded Pt / NiFe(CN)5NO self-supporting electrode, a preparation method thereof, and applications thereof. Background Art

[0002] During water splitting, the oxygen evolution reaction (OER) involves a multi-step four-electron transfer process, and its kinetic rate is much lower than that of the hydrogen evolution reaction (HER), which limits the overall water splitting efficiency. The high overpotential of OER requires additional energy to drive, which directly increases the energy consumption and cost of hydrogen production by electrolysis of water. Due to their excellent catalytic performance and tunable electronic structure, noble metals have become a research hotspot in the field of catalytic materials in recent years and are widely used in green energy and sustainable chemical industries. Although noble metals have many advantages in the field of electrocatalysis, their high cost and scarcity limit their large-scale application.

[0003] Therefore, current research focuses on developing efficient composite catalysts, reducing the use of precious metals, exploring non-precious metal alternatives, and constructing a highly active, durable, earth-abundant, and environmentally friendly non-precious metal OER catalyst for efficient catalytic oxygen evolution reaction (OER) and reduced energy consumption and cost of water electrolysis. In alkaline environments, transition metal (Fe, Co, Ni) compounds have been widely studied due to their variable oxidation states and the presence of three-dimensional electrons, and have good catalytic activity in OER. Nickel-iron electrocatalysts have excellent OER catalytic activity due to their synergistic effect and are considered to be alternatives to precious metal catalysts for OER in alkaline solutions. If a nickel-iron composite self-supporting catalyst with excellent OER performance can be prepared, it will have broad application prospects in water electrolysis applications.

[0004] Furthermore, conventional powdered catalysts require the use of binders or other agents to secure them to a conductive substrate, which increases mass transfer resistance and hinders the functioning of active sites. Binder-secured powdered catalysts are susceptible to detachment from the conductive substrate during prolonged, high-current-density electrolysis, resulting in decreased electrocatalytic performance. Therefore, a method for preparing self-supporting electrodes with high economic benefits, high catalytic activity, and excellent stability is needed. Summary of the Invention

[0005] The present invention aims to provide a low-platinum-loading Pt / NiFe(CN)5NO self-supporting electrode, its preparation method, and application. The present invention utilizes an electrochemical method of anodic oxidation coupled with electrodeposition to produce the Pt / NiFe(CN)5NO self-supporting electrode, which offers the advantages of low cost and high catalytic activity in the oxygen evolution reaction caused by water electrolysis.

[0006] The technical solutions of the present invention are as follows:

[0007] A Pt / NiFe(CN)5NO self-supporting electrode is prepared by using a platinum sheet as an anode and a hydrochloric acid aqueous solution of nickel chloride and potassium ferrocyanide as an electrolyte, and performing electrochemical anodic oxidation coupled with electrodeposition reaction to deposit the Pt / NiFe(CN)5NO self-supporting electrode at the cathode.

[0008] in,

[0009] The cathode serves as a deposition carrier and can be a titanium sheet, a nickel sheet or a copper sheet.

[0010] The preparation method of the Pt / NiFe(CN)5NO self-supporting electrode of the present invention is as follows:

[0011] A platinum sheet is used as an anode, a titanium sheet, a nickel sheet or a copper sheet is used as a cathode, the electrode spacing is maintained at 2 to 3 cm, a hydrochloric acid aqueous solution of nickel chloride and potassium ferrocyanide is used as an electrolyte, and an electrochemical anodic oxidation coupled electrodeposition reaction is performed for 0.5 to 4 hours at a constant voltage of 5 to 30 V and a temperature of 25 to 80° C., thereby depositing a Pt / NiFe(CN)5NO self-supporting electrode at the cathode.

[0012] in,

[0013] Platinum, titanium, nickel, and copper sheets were pretreated as follows before use: ultrasonically cleaned with a mixture of acetone, ethanol, and deionized water in a volume ratio of 3:2:5 for 30 min to remove surface grease, then rinsed with deionized water and dried for later use;

[0014] The platinum sheet, titanium sheet, nickel sheet, and copper sheet are metal platinum, titanium sheet, nickel sheet, and copper sheet with a purity greater than 99%; the thickness of the metal sheet is between 0.05 and 1 mm, the length is between 1.5 and 2.5 cm, and the width is between 0.5 and 1.5 cm;

[0015] The electrolyte is prepared from 98% pure nickel chloride reagent, 99.5% potassium ferricyanide reagent, 36-38% hydrochloric acid reagent and deionized water; in the electrolyte, the nickel chloride concentration is 0.5-4 mmol / L, the potassium ferricyanide concentration is 0.5-4 mmol / L, and the hydrochloric acid concentration is 0.5-2 mol / L;

[0016] Preferably, the electrolyte has a nickel chloride concentration of 0.7562 to 3.0247 mmol / L, a potassium ferrocyanide concentration of 0.6044 to 3.022 mmol / L, and a hydrochloric acid concentration of 0.8 to 1.6 mol / L;

[0017] Preferred reaction conditions: constant voltage 5-20 V, temperature 30-70° C., reaction time 1-3 h;

[0018] The prepared Pt / NiFe(CN)5NO self-supporting electrode has a nanosheet structure, and the platinum loading is 0.005-0.050 mg / cm2 .

[0019] The Pt / NiFe(CN)5NO self-supporting electrode of the present invention can efficiently catalyze the oxygen evolution reaction, reduce the overpotential, and accelerate the reaction kinetics, and has application prospects in the field of water electrolysis.

[0020] The technical principles of the present invention include:

[0021] This method utilizes the electrochemical dissolution of trace amounts of platinum metal at the anode in an acidic electrolyte, along with the electrodeposition of nickel and ferrocyanide ions at the cathode. This method combines nickel and iron elements while controlling the amount of platinum deposited, producing a Pt / NiFe(CN)5NO self-supporting electrode. By optimizing the electrochemical reaction conditions, the catalyst's catalytic activity in the oxygen evolution reaction is enhanced.

[0022] The beneficial effects of the present invention are:

[0023] The present invention uses a high-purity metal sheet as a substrate and adopts an anodic oxidation method coupled with an electrodeposition method to prepare a Pt / NiFe(CN)5NO self-supporting electrode in a hydrochloric acid aqueous solution containing nickel chloride and potassium ferrocyanide. The preparation process of the Pt / NiFe(CN)5NO self-supporting electrode is simple, the requirements for reaction equipment are low, the platinum loading is low, and the economic benefit is high. Self-supporting electrodes with different structures and compositions can be obtained on the metal surface by controlling the electrolyte composition, reaction temperature, reaction voltage and reaction time, thereby improving the electrocatalytic activity and stability of the self-supporting electrode.

[0024] Compared with traditional electrode materials, the Pt / NiFe(CN)5NO self-supporting electrode prepared by the present invention does not require additional binders, conductive agents, and current collectors and can be used directly as an electrode. The integrated structure without binders effectively promotes the exposure of active sites and simplifies electrode processing. It can not only effectively promote electron transfer but also prevent catalyst agglomeration or shedding, and has broad application prospects in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 1.

[0026] Figure 2 : Surface mapping of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 1.

[0027] Figure 3 : X-ray diffraction (XRD) pattern of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 1.

[0028] Figure 4 : Oxygen evolution performance diagram of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 1 in an alkaline system.

[0029] Figure 5 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 2.

[0030] Figure 6 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 3.

[0031] Figure 7 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 4.

[0032] Figure 8 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 5.

[0033] Figure 9 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 6.

[0034] Figure 10 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 7.

[0035] Figure 11 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 8.

[0036] Figure 12 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 9.

[0037] Figure 13 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 10.

[0038] Figure 14 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 11.

[0039] Figure 15 : Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 12.

[0040] Figure 16: Scanning electron microscope (SEM) image of the Pt / NiFe(CN)5NO self-supporting electrode prepared in Example 13. DETAILED DESCRIPTION

[0041] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below with reference to embodiments and drawings, but the scope of protection of the present invention is not limited thereto.

[0042] In the following examples, unless otherwise specified, all reagents can be purchased from conventional sources.

[0043] Example 1

[0044] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0045] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0046] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in an electrolyte. The electrode spacing was maintained at 2 cm, the electrolyte temperature was controlled at 50°C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was removed, the sample surface was cleaned with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode.

[0047] The SEM image of the prepared Pt / NiFe(CN)5NO self-supporting electrode is shown in Figure 1 As shown in the figure, the block-shaped material is NiFe(CN)5NO and the granular material is nano-platinum, and the two are intertwined. Its mapping diagram is as follows Figure 2 As shown in Figure 1, platinum, nickel, iron, carbon, oxygen and nitrogen elements are evenly distributed on the electrode surface. Its XRD pattern is as follows Figure 3 As shown in Figure 3, the Pt / NiFe(CN)5NO self-supporting electrode contains diffraction peaks of Pt, NiFe(CN)5NO and Ti, among which the peak of Ti comes from the titanium substrate.

[0048] Its oxygen evolution performance in alkaline system is as follows Figure 4 As shown, 100mA·cm -2The overpotential of the Pt / NiFe(CN)5NO self-supporting electrode at this current density was 265.6 mV, compared to 378.6 mV for the commercial RuO2 catalyst. The resulting Pt / NiFe(CN)5NO self-supporting electrode exhibited superior oxygen evolution performance compared to the commercial RuO2 catalyst. Electrocatalytic oxygen evolution performance was tested on a Shanghai Chenhua electrochemical workstation (CHI760E). A three-electrode system was employed, with the prepared self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and a Hg / HgO electrode as the reference electrode. The electrolyte was a 1 mol / L KOH solution.

[0049] Example 2

[0050] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0051] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0052] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was maintained at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 8 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 5 As shown, the block-shaped substance is NiFe(CN)5NO.

[0053] Example 3

[0054] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0055] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0056] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was maintained at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 14 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was cleaned with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 6 As shown in the figure, there is an agglomeration phenomenon, and NiFe(CN)5NO and Pt nanoparticles agglomerate into clusters.

[0057] Example 4

[0058] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0059] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0060] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was maintained at 2 cm, the electrolyte temperature was controlled at 30 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 7 As shown, many obvious block-shaped NiFe(CN)5NO aggregates and stacks.

[0061] Example 5

[0062] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0063] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0064] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was maintained at 2 cm, the electrolyte temperature was controlled at 60 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was cleaned with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 8 As shown, agglomeration occurred, and NiFe(CN)5NO blocks were interlaced with Pt nanoparticles.

[0065] Example 6

[0066] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0067] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 4.2 mL of hydrochloric acid (36-38% purity) to 45.8 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.0 mol / L.

[0068] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 9 As shown, the platinum nanoparticles become thinner and NiFe(CN)5NO cubes are deposited on top.

[0069] Example 7

[0070] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0071] An electrolyte was prepared by adding 10 mg of nickel chloride (purity 98%), 30 mg of potassium ferrocyanide (purity 99.5%), and 6.7 mL of hydrochloric acid (purity 36-38%) to 43.3 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferrocyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.6 mol / L.

[0072] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 10 As shown, the platinum nanoparticles become coarser and are interlaced with the NiFe(CN)5NO blocks.

[0073] Example 8

[0074] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0075] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 10 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 0.6044 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0076] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 11 As shown in FIG, the large spherical particles are a complex of NiFe(CN)5NO and platinum.

[0077] Example 9

[0078] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0079] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 50 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 3.022 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0080] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 12 As shown, NiFe(CN)5NO clusters and nano-Pt particles are staggered.

[0081] Example 10

[0082] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0083] An electrolyte was prepared by adding 5 mg of nickel chloride (98% purity), 30 mg of potassium ferrocyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 0.7562 mmol / L, the concentration of potassium ferrocyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0084] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 13 As shown, nanoparticles of platinum are intermixed with bulk NiFe(CN)5NO.

[0085] Example 11

[0086] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0087] An electrolyte was prepared by adding 20 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 3.0247 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0088] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 2 h. After the reaction, the cathode sample was taken out, the sample surface was washed with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 14 As shown, nano-platinum particles and NiFe(CN)5NO clusters are mixed and distributed.

[0089] Example 12

[0090] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0091] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0092] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 1 h. After the reaction, the cathode sample was taken out, the sample surface was cleaned with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 15 As shown in the figure, the block-shaped NiFe(CN)5NO and the granular nano-Pt are mixed and distributed on the substrate.

[0093] Example 13

[0094] Cut the platinum sheet with a thickness of 0.085 mm and the titanium sheet with a thickness of 0.2 mm into 1×2 cm 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and then dried to obtain deoiled and degreased metal platinum electrodes and titanium electrodes.

[0095] An electrolyte was prepared by adding 10 mg of nickel chloride (98% purity), 30 mg of potassium ferricyanide (99.5% purity) and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentration of nickel chloride in the electrolyte was 1.5123 mmol / L, the concentration of potassium ferricyanide was 1.8132 mmol / L, and the concentration of hydrochloric acid was 1.2 mol / L.

[0096] A platinum sheet was used as the anode and a titanium sheet as the cathode, and placed in the electrolyte. The electrode spacing was kept at 2 cm, the electrolyte temperature was controlled at 50 ° C, the reaction voltage was 10 V, and the reaction time was 3 h. After the reaction, the cathode sample was taken out, the sample surface was cleaned with deionized water, and dried to obtain a Pt / NiFe(CN)5NO self-supporting electrode. Its SEM image is shown below. Figure 16 As shown, NiFe(CN)5NO aggregated with platinum to form spherical clusters.

[0097] Comparison of the SEM images of Examples 1, 2, and 3 shows that as the reaction voltage increases, more and more platinum nanoparticles adhere to the surface of NiFe(CN)5NO. When the reaction voltage is low, fewer platinum nanoparticles adhere to the surface of NiFe(CN)5NO, and the reaction performance is average; when the reaction voltage is high, more platinum nanoparticles adhere to the surface of NiFe(CN)5NO, but agglomeration easily occurs, resulting in a decrease in the overall performance of the sample. In Example 1, the reaction voltage is reasonably set, an appropriate amount of platinum nanoparticles adhere to the surface of NiFe(CN)5NO, the overall morphology of the sample is uniform, and the performance is excellent.

[0098] Comparing the SEM images of Examples 1, 4, and 5 shows that as the reaction temperature increases, more platinum nanoparticles deposit on the surface of NiFe(CN)5NO. At lower reaction temperatures, fewer platinum nanoparticles are deposited, resulting in average performance. At higher temperatures, more and coarser platinum nanoparticles are deposited, prone to agglomeration, and overall sample performance deteriorates. In Example 1, the reaction temperature was appropriately set, resulting in an appropriate amount of platinum nanoparticle deposition, a uniform overall sample morphology, and excellent performance.

[0099] Comparing the SEM images of Examples 1, 6, and 7 shows that as the hydrochloric acid concentration increases, the deposit increases and the sample morphology changes accordingly. When the hydrochloric acid concentration is low, the deposited product is small and the reaction performance is average. When the hydrochloric acid concentration is high, the deposited product is large and disordered, with an uneven morphology, and the sample performance decreases. In Example 1, the hydrochloric acid concentration is set appropriately, the overall sample morphology is uniform, and the performance is excellent.

[0100] Comparison of the SEM images of Examples 1, 8, and 9 shows that as the concentration of potassium ferricyanide increases, the amount of deposited NiFe(CN)5NO increases, and the sample morphology changes accordingly. When the concentration of potassium ferricyanide is low, no obvious block-shaped sediment is observed, the amount of deposited NiFe(CN)5NO is small, and the reaction performance is average; when the concentration of potassium ferricyanide is high, the amount of deposited NiFe(CN)5NO is large and disorderly, prone to agglomeration, and the sample performance deteriorates. In Example 1, the potassium ferricyanide concentration is reasonably set, the overall morphology of the sample is uniform, and the performance is excellent.

[0101] From the SEM images of Examples 1, 10, and 11, it can be seen that as the nickel chloride concentration increases, the deposition of nickel increases and the sample morphology changes accordingly. When the nickel chloride concentration is relatively low, the deposited product is relatively small and the reaction performance is average; when the nickel chloride concentration is relatively high, it will be deposited again on the surface of the originally deposited NiFe(CN)5NO sample, or even too much metallic nickel will be deposited, resulting in sample agglomeration, active sites being covered, morphology being uneven, and sample performance being reduced. In Example 1, the nickel chloride concentration is reasonably set, the overall sample morphology is uniform, and the performance is excellent.

[0102] Comparison of the SEM images of Examples 1, 12, and 13 reveals that as reaction time increases, the amount of deposited material increases, and the sample morphology changes accordingly. When the reaction time is short, less product is deposited, and the reaction performance is average. When the reaction time is long, excessive product is deposited, clustering, resulting in an uneven morphology and reduced sample performance. In Example 1, the reaction time was appropriately set, resulting in a uniform overall sample morphology and excellent performance.

[0103] In summary, the reaction conditions in Example 1 are the optimal reaction conditions for the Pt / NiFe(CN)5NO self-supporting electrode, which has a uniform morphology and excellent performance.

[0104] Comparative Example

[0105] Invention Name: A method for preparing nano-platinum-titanium electrodes, CN114289032B

[0106] (1) Under the conditions of anhydrous, oxygen-free and nitrogen protection, a certain amount of platinum source and iron source are added to the surfactant, heated and stirred until completely dissolved to obtain a brown-yellow solution; then the temperature is raised to the reduction temperature at a certain heating rate, and the gas flow is switched to a hydrogen-nitrogen mixture. After a period of reduction, the solution is cooled to room temperature, and the obtained platinum-iron nanoalloy is precipitated with ethanol, dispersed with hexane, and washed alternately for multiple times, and finally dispersed in hexane for storage; (2) Tungsten chloride is added to anhydrous ethanol, stirred and dissolved, and then oleylamine and oleic acid are added as surface modifiers to obtain the precursor. The solution is added to a reactor, and a solvent thermal reaction is carried out at a certain temperature. After cooling to room temperature, the product is washed alternately with cyclohexane and ethanol to obtain tungsten oxide whose surface is modified with oleylamine and oleic acid long carbon chain organic molecules, that is, surface organic matter modified tungsten oxide; (3) a certain amount of platinum-iron nanoalloy of step (1) is weighed and dispersed in a mixed solution of hexane and acetone, a certain amount of surface organic matter modified tungsten oxide of step (2) is added, ultrasonically dispersed, dried, introduced into an inert atmosphere, and treated at a certain temperature for a period of time to obtain the tungsten oxide-supported platinum-iron nanoalloy catalyst.

[0107] By comparison, the present method, which uses an electrochemical process of anodic oxidation coupled with electrodeposition to prepare a Pt / NiFe(CN)5NO self-supporting electrode, features a simple preparation process, easy operation, and minimal reaction equipment requirements. The platinum source used in this method is derived from the metal electrode, requiring minimal amounts, and the platinum sheet is reusable, resulting in lower costs and higher economic benefits.

[0108] The catalyst prepared by this method is a self-supporting structure electrode. Compared with the powder product in the comparative example, it avoids the use of additives such as adhesives. Its integrated structure without the need for binders effectively promotes the exposure of active sites and simplifies electrode processing. It can not only effectively promote the transfer of electrons, but also prevent the agglomeration or shedding of the catalyst, and has broad application prospects in the energy field.

Claims

1. A Pt / NiFe(CN)5NO self-supporting electrode, characterized in that: The method uses a platinum sheet as the anode and a hydrochloric acid aqueous solution of nickel chloride and potassium ferrocyanide as the electrolyte. Through electrochemical anodic oxidation coupled with electrodeposition reaction, a Pt / NiFe(CN)5NO self-supporting electrode is deposited at the cathode.

2. The Pt / NiFe(CN)5NO self-supporting electrode according to claim 1, characterized in that The cathode serves as a deposition carrier and is selected from titanium sheet, nickel sheet or copper sheet.

3. The method for preparing the Pt / NiFe(CN)5NO self-supporting electrode according to claim 1, wherein: The preparation method is as follows: A platinum sheet is used as the anode, a titanium sheet, a nickel sheet or a copper sheet is used as the cathode, the electrode spacing is maintained at 2 to 3 cm, a hydrochloric acid aqueous solution of nickel chloride and potassium ferrocyanide is used as the electrolyte, and an electrochemical anodic oxidation coupled electrodeposition reaction is carried out for 0.5 to 4 hours at a constant voltage of 5 to 30 V and a temperature of 25 to 80° C., and a Pt / NiFe(CN)5NO self-supporting electrode is deposited at the cathode.

4. The preparation method according to claim 3, wherein The platinum sheet, titanium sheet, nickel sheet, and copper sheet were pretreated as follows before use: ultrasonically cleaned with a mixed solution of acetone, ethanol, and deionized water in a volume ratio of 3:2:5 for 30 minutes to remove surface grease, then rinsed with deionized water, and dried for later use.

5. The preparation method according to claim 3, wherein In the electrolyte, the nickel chloride concentration is 0.5-4 mmol / L, the potassium ferrocyanide concentration is 0.5-4 mmol / L, and the hydrochloric acid concentration is 0.5-2 mol / L.

6. The preparation method according to claim 5, wherein In the electrolyte, the nickel chloride concentration is 0.7562-3.0247 mmol / L, the potassium ferrocyanide concentration is 0.6044-3.022 mmol / L, and the hydrochloric acid concentration is 0.8-1.6 mol / L.

7. The preparation method according to claim 3, wherein Reaction conditions: constant voltage 5-20 V, temperature 30-70° C., reaction time 1-3 h.

8. The preparation method according to claim 3, wherein The prepared Pt / NiFe(CN)5NO self-supporting electrode has a nanosheet structure, and the platinum loading is 0.005-0.050 mg / cm 2 .

9. Use of the Pt / NiFe(CN)5NO self-supporting electrode as claimed in claim 1 in catalytic oxygen evolution reaction.